2017
DOI: 10.4236/gep.2017.58007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maize/Haricot Bean Intercropping on Soil Fertility Improvement under Different Tied Ridges and Planting Methods, Southeast Ethiopia

Abstract: Mono cropping is the dominant factor influencing plant nutrient uptake and loss of soil quality in Ethiopia whereas intercropping of cereal/legume has positive environmental qualities. Likewise drought and moisture stress condition is widely expanding from all direction to the center of the country. Therefore, the objective of this research was to evaluate influence of planting methods, tied ridge and cropping system on different soil chemical properties in case of Madda Walabu district, Southeast Ethiopia. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
5
1
0
Order By: Relevance
“…For example, the intercrops had a higher SOC compared to the preplanting soil and sole maize, and this could be because of the component crops contributed much litter falls into the soil environment. These results were similar to those of Hirpa [ 44 ] and Beshir and Abdulkerim [ 45 ] who found that maize-haricot bean intercropping produced a greater amount of SOC compared to the preplanting soil and sole maize. Maize intercropped with haricot bean offered a 9% higher SOC than the preplanting soil [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, the intercrops had a higher SOC compared to the preplanting soil and sole maize, and this could be because of the component crops contributed much litter falls into the soil environment. These results were similar to those of Hirpa [ 44 ] and Beshir and Abdulkerim [ 45 ] who found that maize-haricot bean intercropping produced a greater amount of SOC compared to the preplanting soil and sole maize. Maize intercropped with haricot bean offered a 9% higher SOC than the preplanting soil [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…These results were similar to those of Hirpa [ 44 ] and Beshir and Abdulkerim [ 45 ] who found that maize-haricot bean intercropping produced a greater amount of SOC compared to the preplanting soil and sole maize. Maize intercropped with haricot bean offered a 9% higher SOC than the preplanting soil [ 45 ]. Soils under the intercrops had higher TN than soils in the preplanting soil and sole maize.…”
Section: Discussionsupporting
confidence: 90%
“…According to these results, all monocropping systems showed low O.M. content compared to cereallegume intercropping combinations, which is in line with the ndings of a study by Beshir and Abdulkerim [19], who observed an increase in O.M. content in the soil after cereal-legume intercropping system as compared to the mono-cropping system.…”
Section: Levels Of Soil Organic Matter In Different Cereal-legume Int...supporting
confidence: 90%
“…7). The results also show that all monocropping systems contained low nitrogen content compared to cereal-legume intercropping combinations, which is in line with the ndings of a study by Ngwira et al [23], Beshir and Abdulkerim [24]; and Fu et al [25], who reported enhanced soil fertility by intercropping through nitrogen-xation. Therefore, the cereal-legume combinations in the intercropping systems provided favorable conditions for biological nitrogen xation…”
Section: Soil Nitrogen (%) Under the Cereal-legume Intercropping Comb...supporting
confidence: 90%
“…Previous studies have shown that tied-ridge, which is a proven method of maintaining soil moisture at 0–5 and 6–10 cm soil depth in drier periods in rain-fed agriculture, increases yield by 50% ( Mandumbu et al, 2020 ; Sibhatu et al, 2017 ). Beshir & Abdulkerim (2017) revealed an increase in soil fertility with in-furrow planting in a closed-end tied-ridge system. Consequently, Mupangwa, Love & Twomlow (2006) reported an average maize yield of 3,400 kg ha -1 from tied ridges compared with 1,500 kg ha -1 from conventionally ploughed fields.…”
Section: Introductionmentioning
confidence: 99%